2016
DOI: 10.1590/1413-81232015217.18602014
|View full text |Cite
|
Sign up to set email alerts
|

Stunting in children under five years old is still a health problem in the Western Brazilian Amazon: a population-based study in Assis Brasil, Acre, Brazil

Abstract: Despite the process of nutritional transition in Brazil, in some places, such as the Amazon region, stunting is still an important public health problem. We identified the prevalence and factors associated with stunting in children under five years old residing in the urban area of Assis Brasil. A survey was conducted in which a questionnaire on socioeconomic, maternal and children's conditions was applied, and height or length was measured. The children with height for age index below -2 Z-scores were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
2
4
0
7
Order By: Relevance
“…India carries the second largest population share in the world with diverse culture and dietary habits 5 . Therefore, it is essential to incorporate these diversities into consideration while making plans and policies.…”
mentioning
confidence: 99%
“…India carries the second largest population share in the world with diverse culture and dietary habits 5 . Therefore, it is essential to incorporate these diversities into consideration while making plans and policies.…”
mentioning
confidence: 99%
“…Mantovani et al 25 evaluated the height for age in children aged under 5 years old in one AC municipality and found that stunting is still present with a prevalence of 14.4% of the sample. Low stature for age may indicate accumulated malnutrition over a long period, adversely affecting health and often without possibility of recovery, impeding the full physical development of children.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian menunjukkan anak (6-23 bulan) yang stunting selain memilki tingkat IQ yang lebih rendah, mereka juga memiliki penilaian lebih rendah pada psikomotor (Adeba, Garoma, Gemede, dan Garoma, 2014) . Koordinasi tangan dan mata, pendengaran, berbicara, dan kinerja jika dibandingkan dengan anak normal (Mantovani, et al, 2016).…”
Section: Pendahuluanunclassified